2013
DOI: 10.7747/jfs.2013.29.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Chittagong University Campus: Rich in Forest Growing Stock of Valuable Timber Tree Species in Bangladesh

Abstract: The campus of Chittagong University in Bangladesh is rich in forest ecosystem. The campus has large area with vast tract of land planted with valuable timber tree species. The present study identifies and discovers the potential growing stock of the plantations in the campus area. This Growing stock was measured in three parameters viz. volume, biomass and organic carbon stock. Study identified thirty three economically valuable forest tree species in the plantations of Chittagong University. Out of three grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In majority of the studies, below-ground carbon stock was calculated as 15% of above-ground carbon stock (Miah, Uddin, Bhuiyan, Koike, & Shin, 2009;Ullah & Al-Amin, 2012), but in another study, it was found 14% in real field (Rahman et al, 2015) which added further errors into the estimates. In addition, confusion compounded when someone used 0.50 (Dey et al, 2014;Islam, 2013;Shin et al, 2007) as the carbon conversion factor from biomass and some other used 0.58 (Akter, Rahman, & Al-Amin, 2013;Sohel et al, 2015). Similarly, Rahman et al (2013)…”
Section: Forest Areas Covered: Spatial Distribution Of Existing Studiesmentioning
confidence: 99%
“…In majority of the studies, below-ground carbon stock was calculated as 15% of above-ground carbon stock (Miah, Uddin, Bhuiyan, Koike, & Shin, 2009;Ullah & Al-Amin, 2012), but in another study, it was found 14% in real field (Rahman et al, 2015) which added further errors into the estimates. In addition, confusion compounded when someone used 0.50 (Dey et al, 2014;Islam, 2013;Shin et al, 2007) as the carbon conversion factor from biomass and some other used 0.58 (Akter, Rahman, & Al-Amin, 2013;Sohel et al, 2015). Similarly, Rahman et al (2013)…”
Section: Forest Areas Covered: Spatial Distribution Of Existing Studiesmentioning
confidence: 99%
“…From each section of each beat, five plots of size 10 m  10 m (using Gareth's method Gareth 1991) were selected randomly for growth (stems per unit area, DBH and height of trees) data collection. A complete randomized block design was followed for taking samples from the sample plots (Akter et al 2011(Akter et al , 2013. Primary data was collected from 90 randomly selected plots.…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…Reports found that a healthy forest can sequester almost 150 to 300 tonne carbon per hactre area. Where, plantation in Chittagong University campus can store 107.48 tonneC/ha (Akter et al 2013). If one tonne carbon dioxide equivalent price is 50 USD in near future then the carbon value of a living forest is about 7,500-15,000 USD per hactre area.…”
Section: Carbon Creditsmentioning
confidence: 99%
“…The potential organic carbon in forest stands is almost 92 tC/ha especially in the natural hill forest of Bangladesh (Miah et al 2011) where Akter et al (2013) found this to be 150-300 tC/ha in managed plantation forest. Brown et al (1993) found this to be 255 tC/ha in potential biomass, 144 tC/ha in actual biomass and 148 tC/ha in soils within Asia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation